Sound in the landscape, a study of the historical literature. Part 3a: the sixteenth century onwards. (2nd January 2021) - Hooke, Della
ABSTRACT: The sixteenth century witnesses a renewed interest in the sounds issuing from the country pursuits of ordinary folk of the countryside. It will not be until the nineteenth century that the systematic recording of folk songs was to begin but a number of writers were already including mentions of countryside sounds and songs of country folk into their works. The sound of birdsong, however, continues to reign supreme among 'natural' sounds, with weather, trees and water also playing a role. These themes continue in poetry and literature throughout the succeeding centuries. A selection of quotations from poetry and other literary sources are given here.